Exploring the influence of donor physiognomic factors on packed red cell unit quality: A retrospective analysis from a tertiary care transfusion center - P. Nagaraju; Shashank Ojha; Suryatapa Saha (Asian Journal of Transfusion Science)
BACKGROUND: Donor physiognomic characteristics play a critical role in determining the quality of packed red cell units (PRBCs), which directly impacts transfusion outcomes. This retrospective study aimed to evaluate the influence of donor physiognomic factors on PRBC quality at a tertiary care transfusion center. METHODS: A retrospective analysis was conducted on 250 randomly selected blood donors from January 2015 to August 2018. Donor age, gender, weight, and predonation hemoglobin (PHB) levels were assessed, along with PRBC parameters including volume (350 ml vs. 450 ml), processing method, PRBC age, and percent hemolysis during storage. Subsequent evaluations included hematocrit, per unit total hemoglobin (UTHB), and red cell mass. RESULTS: The mean weight among donors aged 18–28 years was 69.8 kg, compared to 74.46 kg in higher age groups. Lower PHB levels (12.5–13.0 g/dL) were associated with decreased UTHB. PRBCs prepared using the buffy coat method exhibited lower mean UTHB compared to other methods. A significant correlation (P = 0.01) was observed between PRBC age and hemolysis in all units. CONCLUSIONS: Donor PHB significantly influences the quality of PRBCs prepared, with lower PHB levels correlating with decreased UTHB. PRBCs prepared using the buffy coat method showed inferior UTHB, and older PRBC units displayed higher red cell hemolysis. However, donor gender, age, and weight did not significantly affect PRBC quality in this study. Larger sample sizes are necessary to confirm these findings. These results highlight the importance of donor screening and selection to optimize PRBC quality and enhance transfusion therapy outcomes.